The parasympathetic and sensory innervation of the proximal and distal colon in male mice - Wang, Lixin; Taché, Yvette (Frontiers in Neuroanatomy, 2024)
Introduction The distributions of extrinsic neurons innervating the colon show differences in experimental animals from humans, including the vagal and spinal parasympathetic innervation to the distal colon. The neuroanatomical tracing to the mouse proximal colon has not been studied in details. This study aimed to trace the locations of extrinsic neurons projecting to the mouse proximal colon compared to the distal colon using dual retrograde tracing. Methods The parasympathetic and sensory neurons projecting to colon were assessed using Cholera Toxin subunit B conjugated to Alexa-Fluor 488 or 555 injected in the proximal and distal colon of the same mice. Results Retrograde tracing from the proximal and distal colon labeled neurons in the dorsal motor nucleus of the vagus (DMV) and the nodose ganglia, while the tracing from the distal colon did not label the parasympathetic neurons in the lumbosacral spinal cord at L6-S1. Neurons in the pelvic ganglia which were cholinergic projected to the distal colon. There were more neurons in the DMV and nodose ganglia projecting to the proximal than distal colon. The right nodose ganglion had a higher number of neurons than the left ganglion innervating the proximal colon. In the dorsal root ganglia (DRG), the highest number of neurons traced from the distal colon were at L6, and those from the proximal colon at T12. DRG neurons projected closely to the cholinergic neurons in the intermediolateral column of L6 spinal cord. Small percentages of neurons with dual projections to both the proximal and distal colon existed in the DMV, nodose ganglia and DRG. We also observed long projecting neurons traced from the caudal distal colon to the transverse and proximal colon, some of which were calbindin immunoreactive, while there were no retrogradely labeled neurons traced from the proximal to distal colon. Discussion These data demonstrated that the vagal motor and motor and sensory neurons innervate both the proximal and distal colon in mice, and the autonomic neurons in the intermediate zone of the lumbosacral spinal cord do not project directly to the mouse colon, which differs from that in humans.